A qualitative investigation into the role of the caddie in elite-level golf - Pilgrim, J.; Robertson, S.; Kremer, P. (International Journal of Sports Science & Coaching, 2016)
The aim of this study was to determine the nature of the caddie's role in the decision-making, psychological conditioning and tournament preparation of elite-level golfers. Semi-structured interviews were conducted with 17 elite-level golfers (17-24 years; 15 males and 2 females) and 6 caddies (29-42 years; 6 males). Data were transcribed and subjected to thematic analysis techniques. Analysis produced four main findings: (1) the caddie's role in decision-making was to provide information, assist in shot selection, and provide feedback of the golfer`s club selection; (2) the caddie`s role in psychological conditioning was to maintain the golfer`s high performance state using a variety of cognitive and attentional strategies; (3) caddies assist in tournament preparation by `mapping' to plan strategy and record the important characteristics of the course prior to a competitive event; and (4) although the benefits of the caddie were recognised, golfers were dissatisfied with the quality of caddies available. The findings of this study provide guidelines for the best practice of caddies. Additionally, the development of a prerequisite document or `caddie contract` was proposed as an appropriate solution to the issue of golfer discontent in caddie quality. The application of this knowledge has implications for National Sporting Organisations, performance enhancement in the sport, and the development of more effective working relationships between elite golfers and their caddies. ABSTRACT FROM AUTHOR